Analisis Faktor Penyebab Keterlambatan Pengembalian Rekam Medis Rawat Inap di Rumah Sakit X - Sabran, Sabran; Angelina, Alvia Irin; Alfiansyah, Gamasiano; Mudiono, Demiawan Rachmatta Putro; Deharja, Atma (Politeknik Negeri Jember, 2025)
Delays in the return of inpatient medical records at Hospital X reached 25.01%, which is far below the required standard of 100% completion within 2×24 hours. This study aims to analyze the factors contributing to these delays using a qualitative approach. The main informants were medical record officers, and data were collected through interviews, observations, and documentation, with validity ensured through source and method triangulation. The findings show that predisposing factors include mismatched educational background, limited knowledge, and staff attitudes related to the completeness of signatures from attending physicians and nurses. Enabling factors involve the long distance between inpatient wards and the medical record unit, as well as the absence of elevator facilities for transporting records. Reinforcing factors include the lack of penalties for delayed returns and insufficient understanding of the physical form and standard operating procedures for medical record return. Improvement efforts include staff training, socialization of medical record completeness requirements, procurement of dedicated transport facilities for records, and regular revision and dissemination of standard operating procedures. The hospital is advised to strengthen monitoring, improve inter-unit coordination, provide efficient record transportation systems, and implement a reward and punishment mechanism to enhance the timeliness of inpatient medical record returns.